313 DIAGNOSES ASSOCIATED WITH ATYPICAL ANTIPSYCHOTIC USE IN PRIVATELY INSURED CHILDREN. Issue 1 (1st January 2007) - Halloran, D. R.; Swindle, J.; Takemoto, S. K.
Abstract : Background: Atypical antipsychotic medications have not been carefully studied in children. Studies, however, have shown a dramatic increase in their use, with a prevalence of 13 per 1, 000 children in a Midwestern Medicaid population in 2001 for psychiatric diagnoses such as attention-deficit, conduct, and mood disorders. Objective: To evaluate the prevalence of atypical antipsychotics in commercially insured children and the diagnoses associated with treatment. Methods: Prescription and medical claims were used to conduct a retrospective cohort study of children 2 to 18 years of age covered by a large private insurance agency in the Midwest. The prevalence of children receiving atypical antipsychotics between January 2002 and December 2005 was determined along with associated diagnoses. We used chi-square tests for statistical comparisons. Results: The study population included 198, 849 children with a mean age of 10.3 years (SD = 5.0). A total of 2, 305 children received at least one prescription for an atypical antipsychotic (11.6 per 1, 000 children). Children prescribed atypical antipsychotics were 64% male and had a mean age of 12.3 years (SD = 3.8). Males were 1.7 times more likely to receive atypical antipsychotics than females (95% CI 1.6, 1.9). Children 10 years of age and older were 2.5 times more likely to be prescribed atypical antipsychotics than children less than 10 years (95% CI 2.3, 2.8). The most common diagnoses were disruptive behavior disorders (65%), mood disorders (64%), and anxiety disorders (45%). The majority (74%) of children had more than one diagnosis. Males on atypical antipsychotics were 2.5 times more likely to have a diagnosis of disruptive disorder (95% CI 2.1, 3.0), whereas females were 1.6 times more likely to have a diagnosis of a mood disorder (95% CI 1.4, 2.0) and 1.4 times more likely to have an anxiety disorder (95% CI 1.2, 1.7). Children 10 to 14 years of age on atypical antipsychotics are 2.8 times more likely to have a diagnosis of disruptive disorder than children 15 to 18 years old (95% CI 2.3, 3.4), whereas children 15 to 18 years of age were 1.7 times more likely to have a diagnosis of a mood disorder than children 10 to 14 years old (95% CI 1.4, 2.1). A total of 173 children (7.5%) had no psychiatric diagnosis coded during the study period. Conclusions: The rate of atypical antipsychotic use in privately insured youth is similar to that of a Medicaid population (11.6 vs 13 per 1, 000). Although disruptive behavior disorders are the primary diagnoses in youth on atypical antipsychotics, the majority of children prescribed an atypical antipsychotic have multiple psychiatric diagnoses. Studies are needed to assess the risk-benefit ratio and long-term safety and efficacy in these patients.